Buket Sebagai Karya Seni - M. Faiz; Sabrina Azlianty; Yeyen Zefania Tobing; Osberth Sinaga (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
Bouquets have evolved from mere flower arrangements into a work of art that combines elements of aesthetics, creativity, and innovation. This study aims to examine bouquets as an art form by highlighting aesthetic elements, arrangement techniques, and their role in the creative industry. The method used in this study is descriptive qualitative with a literature study approach from various relevant journal references and articles. The results of the study indicate that bouquets not only have aesthetic value but also reflect artistic expression through the selection of colors, shape compositions, and various arrangement techniques. Innovations in making bouquets, such as the use of flannel, snacks, and recycled materials, are expanding the scope of bouquet art in the creative industry. In addition, bouquet art also contributes to the development of the community's economy through increasing business opportunities. Although bouquet art faces challenges such as market competition and fluctuations in raw material prices, its prospects remain promising with the development of technology and product personalization trends. Therefore, continuous innovation is needed so that bouquet art remains relevant and can continue to develop as part of the wider creative industry.